If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 13 = 9x + -11 Reorder the terms: 13 + 3x = 9x + -11 Reorder the terms: 13 + 3x = -11 + 9x Solving 13 + 3x = -11 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 13 + 3x + -9x = -11 + 9x + -9x Combine like terms: 3x + -9x = -6x 13 + -6x = -11 + 9x + -9x Combine like terms: 9x + -9x = 0 13 + -6x = -11 + 0 13 + -6x = -11 Add '-13' to each side of the equation. 13 + -13 + -6x = -11 + -13 Combine like terms: 13 + -13 = 0 0 + -6x = -11 + -13 -6x = -11 + -13 Combine like terms: -11 + -13 = -24 -6x = -24 Divide each side by '-6'. x = 4 Simplifying x = 4
| 5y^3-8y^2+3y=0 | | 8x^2=7x+3 | | 50+2y=5y | | (x+2)(x-3)(3x+4)=0 | | -5y+7x=105 | | -67-8x=86-38x | | x^2+8kx+x=0 | | 18*1.6= | | -9-3x=3x+10 | | 3d+5=10 | | .4x+.3=3.5 | | 3+2x+3x-4x=15 | | 10x+6-9x=10 | | 20x-9=12x-98 | | 14+2x+4-x=32 | | 7+x=2*x | | 7+y=2*y | | 7+y=2xy | | x+3(x-3)=0 | | 36x^5-36x^4+6x^3-6x^2=0 | | 10-y=y+2 | | (24-x)-(19-2x)=11 | | 4-3(3x-2)=-5 | | x^2-2x-4y+9=0 | | 12y-12=4y+4 | | 5(-2+t)+4= | | z^3=-27 | | 2b-4b=4 | | (8t+13)+(-3t+7)= | | -6+5t= | | 8t-16=40 | | 33-17= |